2012
DOI: 10.1126/scitranslmed.3002868
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Targeting of Toll- and Nod-Like Receptors Induces Effective Tumor-Specific Immune Responses

Abstract: Toll-like receptor (TLR) ligands are increasingly being used as adjuvants in cancer vaccine trials to harness innate immunity and prime effective antitumor immune responses. Despite some success, enhancing tumor antigen presentation, promoting a protective antitumor response, and overcoming the immunosuppressive tumor microenvironment pose considerable challenges that necessitate further improvements in vaccine design. Here, we show that expression of the TLR ligand flagellin within tumor cells constitutes an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 60 publications
0
104
0
4
Order By: Relevance
“…In fact, activation of TLR5 by commensal bacteria was shown to drive malignant progression at extramucosal locations through the promotion of inflammation, which dampened antitumor immunity by expanding immunosuppressive networks (65). In contrast, we and others have shown that TLR5 activation has tumor growth suppressive effects and stimulates antitumor immunity (19)(20)(21)(22)(23)(24)(25)(26)53). Earlier studies in our laboratory showed that entolimod displayed a growth-inhibitory effect on a TLR5-expressing mouse xenograft model of human lung adenocarcinoma A549 (23), supporting a direct effect of TLR5 stimulation on tumor growth suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, activation of TLR5 by commensal bacteria was shown to drive malignant progression at extramucosal locations through the promotion of inflammation, which dampened antitumor immunity by expanding immunosuppressive networks (65). In contrast, we and others have shown that TLR5 activation has tumor growth suppressive effects and stimulates antitumor immunity (19)(20)(21)(22)(23)(24)(25)(26)53). Earlier studies in our laboratory showed that entolimod displayed a growth-inhibitory effect on a TLR5-expressing mouse xenograft model of human lung adenocarcinoma A549 (23), supporting a direct effect of TLR5 stimulation on tumor growth suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the only known natural TLR5 agonist, flagellin, flagellin-expressing Salmonella bacteria, and a pharmacologically optimized flagellin derivative named entolimod (CBLB502) have antitumor effects in several tumor models (19)(20)(21)(22)(23), including mouse models of liver metastases (24)(25)(26). Moreover, systemic administration of TLR5 agonists is uniquely safe because of the restricted pattern of expression of TLR5 (primarily in the gut, liver, and bladder) and the nature of the cytokines induced following TLR5 stimulation.…”
mentioning
confidence: 99%
“…A few studies to date suggest that such synergies may also be relevant for in vivo responses to vaccination. For example, a cancer vaccine based on irradiated flagellin-and ovalbuminexpressing tumor cells was shown to elicit potent T cell responses in mice, dependent on both TLR5 and the Nod-like receptors NLRC4 and NAIP5 (72). In NHPs, combinations of TLR7/8 and TLR9 agonists enhanced the induction of binding and neutralizing antibody titers against an HIV envelope immunogen (73).…”
Section: Codelivery Of Antigen and Danger Signalsmentioning
confidence: 99%
“…[29]. Nous avons récemment montré que des cellules tumorales modifiées de telle façon qu'elles expriment la flagelline stimulent efficacement les cellules myéloïdes et génèrent une réponse adaptative spécifique d'antigènes tumoraux [30]. Une telle stratégie pourrait s'avérer prometteuse comme traitement prophylactique ou curatif dans des modèles murins de tumeurs [30].…”
Section: Assimiler Les Nouveaux Concepts Pour Développer De Nouveaux unclassified
“…Nous avons récemment montré que des cellules tumorales modifiées de telle façon qu'elles expriment la flagelline stimulent efficacement les cellules myéloïdes et génèrent une réponse adaptative spécifique d'antigènes tumoraux [30]. Une telle stratégie pourrait s'avérer prometteuse comme traitement prophylactique ou curatif dans des modèles murins de tumeurs [30]. Elle présente plusieurs avantages : (1) elle permet de cibler deux types de PRR complémentaires en délivrant les ligands correspondants à l'endroit où sont localisés leurs récepteurs ; (2) elle assure la présence du ligand de TLR5 dans le phagosome contenant les cellules tumorales et favorise ainsi la « reconnaissance associative » d'une multitude d'antigènes tumoraux, ne limitant pas cette approche aux seuls cancers dont certains antigènes ont préala-blement été identifiés (Figure 3).…”
Section: Assimiler Les Nouveaux Concepts Pour Développer De Nouveaux unclassified